Analisis Penerimaan Sistem Informasi Akademik Mahasiswa (SIAM) Institut Teknologi Garut Menggunakan Metode Technology Acceptance Model - Asri Mulyani; Muhammad Rikza Nashrulloh; Ai Karlina (Jurnal Algoritma, 2022)
Garut Institute of Technology implements an academic information system for students as an educational institution. When an institution implements an information system, user acceptance must be considered. There has never been an evaluation of user acceptance of the system since it was implemented. This study examines student acceptance of system users using the Technology Acceptance Model Method. Evaluation data, and questionnaires were sent to active students of the Garut Institute of Technology, with a total of 1,681 respondents and a sample size of 200. The results supported only two of the five hypotheses tested in this study. One of them is that the E-Resources Organization has a positive effect on Perceived Ease of Use, with a probability value of 0.000 or less than 0.05 which indicates that the effect is significant at the 5% significance level. E-Resources organization has no effect on Perceived Ease of Use with a probability value of 0.077 or greater than 0.05 indicating no significance at a significance level of 5%, Perceived Ease of Use does not affect Perceived Usability with a probability value of 0 0.437 or greater than 0 .05, and Perceived Ease of Use has no effect on Attitude of Use with a probability value of 0.385 or greater than 0.05.